2016
DOI: 10.1002/cphc.201600165
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Boron Nitride Nanosheets with Model Cell Membranes

Abstract: Boron nitride nanomaterials have attracted attention for biomedical applications, due to their improved biocompatibility when compared with carbon nanomaterials. Recently, graphene and graphene oxide nanosheets have been shown, both experimentally and computationally, to destructively extract phospholipids from Escherichia coli. Boron nitride nanosheets (BNNSs) have exciting potential biological and environmental applications, for example the ability to remove oil from water. These applications are likely to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Therefore, we tested two sets of partial atomic charges for B and N atoms-PAC-I Q B = 1.05 e, Q N = −1.05 e; PAC-II Q B = 0.5 e, Q N = −0.5 e-in accordance with Ref. [65]. For instance, two PAC sets of ±1.05 e and ±0.4 e were also used for the boron nitride 2dNM model [66].…”
Section: Boron Nitride Nanosheet Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we tested two sets of partial atomic charges for B and N atoms-PAC-I Q B = 1.05 e, Q N = −1.05 e; PAC-II Q B = 0.5 e, Q N = −0.5 e-in accordance with Ref. [65]. For instance, two PAC sets of ±1.05 e and ±0.4 e were also used for the boron nitride 2dNM model [66].…”
Section: Boron Nitride Nanosheet Modelsmentioning
confidence: 99%
“…Because of a strong dependence of the partial atomic charges of boron nitride nanomaterials on the environment [64], we examined two sets of partial atomic charges selected by using a method in Hilder and Gaston [65]: ±1.05 e (PAC-I) and ±0.5 e (PAC-II), with a negative value for nitrogen and a positive value for boron atoms. Despite the significant difference in the partial charges, the obtained estimates of the free energy of adsorption for the head and tail parts of the POPC lipid are close to each other (Figure 5a,b, blue curves).…”
Section: Boron Nitride Nanosheetsmentioning
confidence: 99%
“…For instance, hBN nanotubes were observed to be spontaneously attracted by lipid bilayers and form stable lipid insertion, [ 38 ] while hBN nanosheets were found only interacting with the polar head groups of lipid molecules, but not passively crossing the lipid bilayer. [ 39 ] In addition, lipid extraction of hBN nanosheets was noticed to be temperature‐dependent. [ 40 ] At this point, a fundamental biophysical understanding of how hBN interacts with cell membranes remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…[ 40 ] At this point, a fundamental biophysical understanding of how hBN interacts with cell membranes remains largely unexplored. [ 39,41–43 ]…”
Section: Introductionmentioning
confidence: 99%
“…A previous theoretical study based on molecular dynamics simulations showed the interaction of BN nanoakes with model cell membranes and demonstrated the spontaneous attraction of BN nanoakes to the polar head groups of bilayer lipids. 21 Several in vitro and in vivo studies carried out with carbonbased materials demonstrated the dose-, time-, and shapedependent toxicity towards living cells, including human ones. 8,22,23 Interestingly, BN and its derivatives, such as BN nanotubes, seem to be less toxic and more biocompatible than graphene based materials.…”
Section: Introductionmentioning
confidence: 99%